Android Recipes: A Problem-Solution Approach for Android 5.0 - Smith, Dave (Springer, 2015)
Android Recipes, Fourth Edition offers more than 100 down-to-earth code recipes, and guides you step-by-step through a wide range of useful topics using complete and real-world working code examples. This book is updated to include the Android 5.0 SDK, as well as earlier releases.